Literature as a Museum: Gardens between Nature and History - Gabrieloni, Ana Lía (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
In dialogue with the history of formal painting we intend to recover and reflect on literary imagery gathered in musées imaginaires. Imagery that falls outside traditional aesthetic categories underlying the origin and development of the genre, and provides instead a new landscape motif to the classical repertoire of "loci horridi". Rare or distinctly unverifiable in traditional painting, ruined gardens as they are described in two novels by Gustave Flaubert and Virginia Woolf lead to consider of the restorative/museum function of Literature at the heart of visual culture. At the same time, these extraordinarily original gardens, which can be seen as "landscape of devastation", claim for an unrestricted and inclusive art history alternative to the canonical one where no place seems left for them until the beginning of the last century. Accordingly, we propose to conceive of a nautral history of art which allows recognizing and thinking about images not only through literature and painting, but also through the history of nature and the history of humanity, not diametrically opposed but mutually complementary. Interlaced and crucially determining each other as in the novel Nevermore recently published by the French writer and translator, Cécile Wajsbrot, who finds in nature left to her own in the garden depicted in "Time Passes" by Woolf the most "disturbing and tragic" image of the devastation in history.
Keywords: musée imaginaire; literature and painting; landscape; garden; locus horridus; catastrophe